2001
DOI: 10.4141/a01-034
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal degradability of neutral detergent insoluble protein of selected protein sources

Abstract: [601][602][603]. Les auteurs ont mesuré la capacité de dégradation des protéines insolubles dans le détergent neutre (PIDN) de diverses sources dans le rumen de deux vaches fistulées. Les drêches de distillerie sont les PIDN les plus facilement dégradables (P < 0,05); viennent ensuite le tourteau de canola chauffé à 125°C (P < 0,05) et le tourteau de canola chauffé à 145°C (P < 0.05) Les résultats indiquent que la capacité de dégradation des PIDN dans le rumen varie avec l'origine des protéines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Fractions A, B 1 and B 2 are normally associated with cell content, while fraction B 3 is associated with plant cell walls. Despite the strengths of this technique, some aspects of the procedure have been criticized, mainly its methodological rigidity and the lack of representation of the biological phenomena that occur in the rumen (Stern et al, 1997;Mustafa et al, 2001). Moreover, some authors have reported large differences in the sizes of the different nitrogenous fractions between samples of a single type of feed, suggesting that local conditions and the method itself are major sources of variation in the characterization of these chemical fractions of proteins (Mullahey et al, 1992;Jones et al, 1995;Reed, 1995;Velásquez and Pichard, 2010b).…”
Section: Methodologies For Predicting Protein Degradability In the Rumenmentioning
confidence: 99%
“…Fractions A, B 1 and B 2 are normally associated with cell content, while fraction B 3 is associated with plant cell walls. Despite the strengths of this technique, some aspects of the procedure have been criticized, mainly its methodological rigidity and the lack of representation of the biological phenomena that occur in the rumen (Stern et al, 1997;Mustafa et al, 2001). Moreover, some authors have reported large differences in the sizes of the different nitrogenous fractions between samples of a single type of feed, suggesting that local conditions and the method itself are major sources of variation in the characterization of these chemical fractions of proteins (Mullahey et al, 1992;Jones et al, 1995;Reed, 1995;Velásquez and Pichard, 2010b).…”
Section: Methodologies For Predicting Protein Degradability In the Rumenmentioning
confidence: 99%